Root Zone Cooling and Exogenous Spermidine Root-Pretreatment Promoting Lactuca sativa L. Growth and Photosynthesis in the High-temperature Season - Sun, Jin; Lu, Na; Xu, Hongjia; Maruo, Toru; Guo, Shirong (Frontiers in Plant Science, 2016)
Root zone high-temperature stress is a major factor limiting hydroponic plant growth during the high-temperature season. The effects of root zone cooling (RZC; at 25°C) and exogenous spermidine (Spd) root-pretreatment (SRP, 0.1 mM) on growth, leaf photosynthetic traits, and chlorophyll fluorescence characteristics of hydroponic Lactuca sativa L. grown in a high-temperature season (average temperature > 30°C) were examined. Both treatments significantly promoted plant growth and photosynthesis in the high-temperature season, but the mechanisms of photosynthesis improvement in the hydroponic grown lettuce plants were different between the RZC and SRP treatments. The former improved plant photosynthesis by increasing stoma conductance (Gs) to enhance CO2 supply, thus promoting photosynthetic electron transport activity and phosphorylation, which improved the level of the photochemical efficiency of photosystem II (PSII), rather than enhancing CO2 assimilation efficiency. The latter improved plant photosynthesis by enhancing CO2 assimilation efficiency, rather than stomatal regulation. Combination of RZC and SRP significantly improved PN of lettuce plants in a high-temperature season by both improvement of Gs to enhance CO2 supply and enhancement of CO2 assimilation. The enhancement of photosynthetic efficiency in both treatments was independent of altering light-harvesting or excessive energy dissipation.